External Adjustment in a Resource-Rich Economy : The Case of Papua New Guinea - Nakatani, Ryota (IMF Working Papers; Working Paper ;, 2017)
How should resource-rich economies handle the balance of payments adjustment required after commodity price declines? This paper addresses the question theoretically by developing a simple two-period multi-sector model based on Nakatani (2016) to compare different exchange rate policies, and empirically by estimating elasticities of imports and commodity exports with respect to exchange rates using Papua New Guinean data. In the empirical part, using various econometric methods, I find the statistically significant elasticities of commodity exports to real exchange rates. In the theoretical part, by introducing the notion of a shadow exchange rate premium, I show how the rationing of foreign exchange reduces consumer welfare. Using the estimated elasticities and theoretical outcomes, I further discuss policy implications for resource-rich countries with a focus on Papua New Guinea.